De significatione vocis "divinae catastrophes" in hymno qui a verbis Iam toto subitus vesper incipit adnotationes quaedam - Gacia, Tadeusz (Vox Patrum, 2025)
The author of a study written in Latin establishes the meaning of the expression divina catastrophe in the breviary hymn for the feast of the Seven Sorrows of the Blessed Virgin Mary Iam toto subitus vesper eat polo, written by Callisto Palombella. He argues against contemporary translations of the hymn, which translate the word catastrophe in an anachronistic way, disregarding the narrower semantic scope of the word at the time of the hymn's composition, and interpret it as God's passion, as God's suffering. Meanwhile, the word catastrophe meant at the time - as in ancient drama - a sudden change of situation, a subversion of order, a turn of events, which makes us see the death of Christ as totius ordinis eversio - a revolution in which all bewildered nature also participates.